Takayasu Arteritis: A Rare Case Report with Ultrasonographic and Color Doppler Features - Ansari, Sajid; Kumar, Abhishek; Dhungel, Kanchan; Ahmad, Kaleem; Sah, Pannalal; Gupta, Mukesh Kumar; Rauniyar, R K; Amanullah, Md. Farid (Journal of Medicine, 2014)
Takayasu arteritis is a rare form of large vessel vasculitis predominantly occurs in young females. Ultrasonography is usually the primary modality of investigation in a patient with signs and symptoms of Takayasu arteritis and features includes wall thickening, luminal narrowing or stenosis, occlusion, luminal dilatation and aneurysms and high resistance flow patterns. Suppression of inflammation and preservation of vascular competence are the aims of treatment. We present the sonographicand color Doppler findings of Takayasu arteritis in a 21 year old female. DOI: http://dx.doi.org/10.3329/jom.v15i1.19878 J Medicine 2014; 15: 71-73